(untitled) (Fourth World Journal, 2025)
This paper examines the exploitation of the Indigenous Oromo people’s natural resources without Free, Prior, and Informed Consent (FPIC), beginning with the historical subjection and oppression of the Oromo by imperial and colonial forces. It challenges the prevailing narrative of Ethiopia’s 3,000-year independence by showing that its current geopolitical boundaries—formed no more than 175 years ago —resulted from African imperial expansion. Focusing on the Lega Dembi gold mines in southern Oromia, the analysis demonstrates how successive Ethiopian regimes have violated Gujii Oromo human and Indigenous rights through forced gold and silver extraction, precipitating severe environmental harm. Finally, it argues for the Oromo Nation’s accession to the International Covenant on the Rights of Indigenous Nations (ICRIN) and recognition by the Nations Indigenous Court Tribunal (NICT), thereby securing a legal forum to address ongoing FPIC infringements and seek redress for resource-extraction abuses. Watch the author discuss the inspiration and key insights behind this article: